ITER-HNB plasma and extraction grids in BUG: Characterization of magnetic deflection correction. Issue 1 (1st April 2022) - Harder, Niek den; Hurlbatt, Andrew; Wimmer, Christian; Orozco, Guillermo; Nocentini, Riccardo; Fröschle, Markus; Heinemann, Bernd; Fantz, Ursel
Abstract: The BATMAN Upgrade test facility aims to extract H - /D - at high current densities. The inevitably co-extracted electrons are deflected out of the beamlet by permanent magnets before acceleration. These magnets induce a row-wise zig-zag deflection of the beamlets. In the new MITICA-like extraction system, this deflection is compensated by additional deflection correction magnets. IBSimu modeling studies indicate that the deflection correction system not only acts on the horizontal beamlet deflection, but also causes aberrations to the vertical angular distribution. Dependencies of the beamlet position and size are studied in several parameter scans with the available diagnostic tools (CFC tile calorimetry, Beam Emission Spectroscopy). The horizontal beamlet deflection is robustly compensated within the systematic uncertainty of the experiment. The triangular beamlet shape predicted on basis of the magnetic field structure is visible in the CFC calorimetry.